OPTIMALISASI UMPANBALIK DALAM PROSES PENILAIAN KARYA: STUDI KASUS PADA YAYASAN X - Gianina Untariady; Rayini Dahesihsari (MANASA, 2016)
In the management of human resources in the organization, planning, succession or regeneration is one way to ensure sustainability of an organization. One of data that can be used to map potential candidates' work is performance appraisal (PA). In other words, an indicator of an effective performance appraisal is how the PA results could be used as a valid reference for succession planning in an organization. At the foundation X, although assessment work based management by objectives (MBO) is applied, but it has not yet used as a reference for succession planning. For that reason, a mapping of the evaluation process to find the phase of performance appraisal that has not run optimally has been done. The interview is used as a technique of collecting the data to 6 respondents, which includes employees whom is assessed, Department Heads whom assess and give feedback, and the Committee whom set the final score of PA. The research results show all stages the evaluation process work based MBO has been implemented. But, the lack of clarity of the feedback process cause the less positive response of employees towards the final score and self-development efforts to be done. Hence, the provision of feedback as part of the evaluation process work is one of the aspects that is essential to be optimized to ensure employee’s positive response of performance appraisal.